Strategi Pondok Pesantren Al Urwatul Wutsqo dalam Menghadapi Tantangan Modernisasi - Moch Sya'roni Hasan; Mar’atul Azizah (Al-Idaroh: Jurnal Studi Manajemen Pendidikan Islam, 2020)
This research to describe the strategy of Urwatul Wutsqo Islamic boarding school dealing with modernization challenges. The focus of his research is the strategy used by Al-Urwatul Wutsqo Islamic Boarding School deal with the challenges of modernization? 2). the activities forms of the Boarding School's deal with it. 3). the supporting and obstacle factors in the implementation it. This study is a qualitative approach in the form of case study. Data collection methods are done through interviews, observation and documentation. Data analysis techniques are data reduction, data display and verification. Al Urwatul Wutsqo's Islamic boarding school strategy dealing with modernization is providing integrated education of faith and piety in accordance with the Qur'an and Hadith. The activities are to love Allah and the hereafter is amal sholih, thariqah, recitation, istighatsah, etc.